Impact Of Cognitive Behavioural Therapy And Mindfulness-Based Therapy On Mental Health And Cognitive Performance: A Socio-Psychological Study In Vadodara, Gujarat - Patel Patel, Amrisha Amitkumar; Singh, Reena (Journal of Neonatal Surgery, 2025)
The Purpose Of This Study Is To Examine How Cognitive Performance And Psychological Health Are Affected By Cbt And Mbt. There Is Encouraging Evidence That Psychological Therapy Can Improve Both Mental Health And Academic Achievement. The Major Objective Of This Research Is To Investigate The Impact Of Motivational Interviewing (Mbt) And Cognitive Behavioral Therapy (Cbt) On Mental Health And The Relationship Between The Two. Three Hundred People In Vadodara, Gujarat, Were Surveyed Using A Quantitative Approach And A Structured Questionnaire. Reliability, Validity, And Structural Model Analysis Were Used To Check The Relationships Between The Constructs. Both Cbt And Mbt, Or Dialectical Behavior Therapy, Have Shown To Be Quite Helpful For Mental Health In Studies. Be That As It May, Cbt Is More Effective. There Is Also Strong Evidence That Indicates A Beneficial Correlation Between Mental Wellness And Cognitive Function. Cognitive Performance, Including Attention, Memory, And Decision-Making, Is Positively Impacted By Factors Such As Better Psychological Well-Being, According To The Research. Emotional Health And Cognitive Performance In Social And Psychological Contexts Can Be Improved By The Incorporation Of Psychological Therapies Into Mental Health Care, According To The Study.